Knowledge, attitude and practice of physical exercises among pregnant women attending prenatal care clinics of public health institutions in Hawassa city, Sidama, Ethiopia, in 2021: descriptive cross-sectional study - Berhan Tsegaye Negash; Yitateku Alelgn (BMC, 2023)
Abstract Background Participating in physical exercise enhances the physical and mental health of pregnant women. Preventing excessive weight gain, decreasing gestational hypertension, reducing back pain and labor complications are some of the main benefits of physical exercise during pregnancy and childbirth. Scrutinizing factors associated with sedentary life style among women during pregnancy could aid to design effective strategies to tackle the problem. Despite its benefit, little is explored about knowledge, attitude and practice of physical exercise among pregnant women in the study setting. Objective To assess prevalence of knowledge, attitude and practice of physical exercise among pregnant women who visit antenatal care at public health facilities of Hawassa town, Ethiopia, in 2023. Methods Facility based survey was conducted from November-December, in 2021. Data were collected using interview administered and structured questionnaire. Data were cleaned, coded and entered using Epi-data 4.6 and exported into SPSS 25 for analysis. Descriptive statistics was done using frequency count, percentage and mean values of variables. Finally, findings are presented using text, tables and charts. Results All of the study subjects completed interview making a response rate of 100% in this study. The mean adequate knowledge score was 42.2%. Positive attitude towards physical exercise during pregnancy was accounted as 63.7% and proportion of good practice of physical exercise was as 35.8%. Regarding practice of exercise, most (95.9%) of the subjects walk, however; only 11(8.9%) women perform pelvic floor exercise were the highest and least practiced physical exercise. Concerning knowledge of exercise, prevent excess weight 72.1% and increasing energy 53.2% were the commonly known benefits of physical exercise. Breathing difficulty (41.3%), chest pain (39.8%) and premature labor (34.0%) were the predominant perceptions of contra-indication of physical exercise during pregnancy. Conclusions In conclusion, the proportion of knowledge, attitude and practice of antenatal exercise is found to be sub-optimum in the study area. Therefore, health education should be enhanced about the benefit of physical exercise during pregnancy.